Periodate activated by manganese oxide/biochar composites for antibiotic degradation in aqueous system: Combined effects of active manganese species and biochar. (1st May 2022) - Fang, Guoge; Li, Jialing; Zhang, Chen; Qin, Fanzhi; Luo, Hanzhuo; Huang, Cheng; Qin, Deyu; Ouyang, Zenglin
Abstract: Developing efficient catalysts for oxytetracycline (OTC) degradation is an ideal strategy to tackle environmental pollution, and advanced oxidation processes (AOPs) have been widely used for its degradation. However, the studies on the activation of periodate (PI) by biochar and its composites in recent years have been scarcely reported. In this study, we focused on the degradation of OTC by PI activation with manganese oxide/biochar composites (Mn x O y @BC). Experimental results showed that the OTC degradation rate of Mn x O y @BC/PI system reached almost 98%, and the TOC removal efficiency reached 75%. Various characteristic analysis proved that PI could be activated efficiently by surface functional groups and manganese-active species (Mn(II), Mn(III), and Mn(IV)) on biochar, and various reactive species such as singlet oxygen ( 1 O2 ), hydroxyl radical (∙OH), and superoxide radical (O2 ∙- ) can be observed via radical quenching experiments. Based on this, three degradation pathways were proposed. Furthermore, Mn x O y @BC and PI were combined to degrade environmental pollutants, which achieved excellent practical benefits and had great practical application potential. We hope that it can provide new ideas for advanced oxidation processes (AOPs) applying for wastewater treatment in the future. Graphical abstract: Image 1 Highlights: Manganese oxide/biochar composites (Mn x O y @BC) had high stability. Periodate (PI) could be activated by active manganese species and biochar. The removal rate of oxytetracycline (OTC) by Mn x O y @BC/PI system was up to 97.5%. O2∙- played the dominant role for the OTC degradation, followed by 1O2 and ∙OH.